Distance analysis of U-turn round facilities for sustainable urban development (case study of Ahmad Yani Road, Tirtayasa and Cilegon road). Issue 1 (October 2021) - Hidayat, B; Saputri, F A A
Abstract: Cilegon City is an industrial city with internal and internal movements occurring on one access road stretching from Jalan Raya Cilegon, Jalan Ahmad Yani, and Jalan Sultan Ageng Tirtayasa. This arterial road section has a total road length of 5 km that passes through the Cilegon City area, which is the center of activity. Efficient use of traffic space by arranging the traffic space efficiency is used the distance between U-turns so that delays and queues are low. As long this road network has the highest volume of 2, 399 pcu/h with an average speed of 32 km/h and reaching a VCR of 0.8 has a median number of 13-point openings, the number of uncontrolled U-turns causes many conflicts traffic that will cause traffic disruption when a vehicle makes a U-turn. The purpose of this study is to improve the performance of the road network in the Area of the City of Cilegon by knowing the best distance between U-Turns. Simulation analysis uses Vissim software to produce the ideal distance for each opening in the Cilegon City arterial road, which is then utilized in the arrange of the U-turn facility itself. The method used is the calculates of existing traffic performance and simulation to determine the ideal distance between U-Turn facilities. The simulation results with the ideal Vissim model of the distance between the turning facilities were 650 meters with an average delay of 17.56 seconds, a network speed of 33.07 km/h, a total distance of 28, 453.34 km, and the total travel time to be 847.30 hours.